Design, Formulation, and Evaluation of Vitamin C Tablets Using Co-Processed Excipient Combination of Jackfruit Seed Starch and Avicel®️ PH 101 - Mayu Rahmayanti; Tanaya Jati Dharma Dewi; Ana Fadilia Aktifa; Sella Paramitha; Rahayu Hikmatul Nikmah; Lumen Muzaidi Septianshar (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Tablet is a popular pharmaceutical dosage form among the public. One method of making tablets is direct compression. This method must consider the flow properties and compressibility of the excipients. But many excipients do not meet these criteria, leading to the alternative use of co-processed excipients of jackfruit seed starch and avicel®️ PH 101. This research aims to determine the physical characteristics of direct compression vitamin C tablets using co-processed excipient of PBN-A (Jackfruit Seed Starch and Avicel®️ PH 101) with varying ratios of 1:3, 3:1, and 1:1. The research methods include powder preparation, powder evaluation, tablet compression, and physical evaluation of tablet. Descriptive and statistical data analysis using one-way ANOVA. The research results show that tablets exhibit favorable physical characteristics in F1, but F2 and F3 show suboptimal hardness and friability values. The statistical analysis results indicate a significant difference with a p-value of (0.000) and post-hoc tests explain that these significant differences are particularly noticeable between F1 and F2, K1, and K2. This study concludes that vitamin C tablets using co-processed excipients of PBN-A with ratios of 1:3, 3:1, and 1:1 exhibit good physical characteristics in all evaluations, except for the hardness and friability of F2 (3:1) and the hardness of F3 (1:1).